2007
DOI: 10.1039/b713101a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of domoic acid to marine sediments and clays

Abstract: Conditional solid-water distribution coefficients (K(d)) for the adsorption of domoic acid (DA) to a series of complex sediments and clays were determined in artificial seawater. K(d) ranged from 5.11 L g(-1) to 0.97 L g(-1), with a corresponding ranking of: kaolinite > Gulf of Mexico sediment > Santa Barbara Basin sediment > Bread and Butter Creek sediment > poorly crystallized kaolin > Ca-montmorillonite > Na-montmorillonite > well crystallized kaolin > diatomaceous earth. Adsorption correlated with the anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Four MRM transitions from protonated DA were monitored: m/z 312 → 266, m/z 312 → 248, m/z 312 → 193, and m/z 312 → 161. DA analysis of the sediment trap samples was performed using similar LC-MS methods as described in Burns & Ferry (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Four MRM transitions from protonated DA were monitored: m/z 312 → 266, m/z 312 → 248, m/z 312 → 193, and m/z 312 → 161. DA analysis of the sediment trap samples was performed using similar LC-MS methods as described in Burns & Ferry (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Some carnivores, like the swimming crab (Polybius henslowii), can contain high levels of DA but there have been no recorded incidents of poisoning in their predator, the yellow-legged gull (Larus cachinnans) that feeds on them almost exclusively (Á lvarez, 1968;Munilla, 1997;Costa et al, 2003). Vertical flux of DA to the sediment appears to be a substantial source of toxin to the benthic food chain (Sekula-Wood et al, 2009 as DA is stable when adsorbed onto sediments (Burns and Ferry, 2007), long after Pseudo-nitzschia blooms have dissipated in the upper water column. There may be a limit in the number of trophic transfers over which DA can still be present at high enough concentrations to cause a toxic event.…”
Section: Food Web Aspects and Potential Ecological Disruptionsmentioning
confidence: 99%
“…Impacts of DA on marine wildlife at various levels within the food web have also been observed, and this toxin is known to contribute to the deaths of seabirds, sea otters, sea lions and whales. The adsorption of DA, especially to sediments (Burns and Ferry, 2007), facilitates its potentially long-lasting impacts, particularly to the benthic food chain. Here we summarize those impacts of DA on marine wildlife as well as our increased knowledge about Pseudo-nitzschia and DA over the last decade, including changes in worldwide range and impacts, phylogeny, physiology, ecology, monitoring and public health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sekula-Wood et al [ 30 , 32 ] found high quantities of DA in sediment traps at a depth of 540 m in the Santa Barbara Basin, (>20,000 ng/g sediment), thereby providing a source of DA to benthic and pelagic feeders. The transport of DA to sub-surface waters is likely mediated by secondary processes, such as fecal pellet production, marine snow aggregation, and adsorption onto the surfaces of particles [ 27 , 32 , 33 , 34 ] that sink rapidly, exceeding 100 m d −1 [ 30 , 32 , 35 ]. These particle transport processes help to explain the presence of DA in benthic food webs in the absence of an ongoing surface bloom [ 36 , 37 ], thereby allowing for the possibility of DA poisoning long after a toxic Pseudo-nitzschia bloom subsides [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%